The Analysis Study of The Relationship of Microbiome Dysbiosis and Risk of Colorectal Cancer: A Comprehensive Systematic Review from a Laboratory Perspective - Dwana, Laksmita; Sinsanta, Sinsanta; Lesmana, Bimantara (Indonesian Journal of Cancer, 2025)
Background: Colorectal cancer (CRC) is a significant global health concern, with rising incidence rates linked to lifestyle and environmental factors. Recent research highlights the potential role of microbiome dysbiosis in CRC development, suggesting that alterations in gut microbiota may influence disease risk and progression. This systematic review aims to evaluate and synthesize laboratory-based research on the relationship between microbiome dysbiosis and risk factors for CRC, along with the risk for its progression. The review assesses methodologies, identifies key microbial markers correlated with risk factors, and explores potential implications for early detection and treatment.Methods: Adhering to PRISMA 2020 guidelines, the review focused on studies from 2014 to 2024, examining microbiome dysbiosis and CRC risk. Databases searched included PubMed, ScienceDirect, and SagePub. Inclusion criteria comprised English-language studies on laboratory-based microbiome analysis related to CRC. The review process involved a three-level screening to select relevant studies, followed by a detailed quality assessment.Results: Out of numerous publications, eight key studies were included. This review emphasizes the evolving role of microbiome-based biomarkers in CRC detection and management. Key studies highlight the potential for integrating microbial markers and metabolomics into clinical practice to improve early diagnosis and therapeutic strategies. The findings suggest that microbiome dysbiosis can significantly impact CRC risk and progression, providing a foundation for future research and clinical applications.Conclusions: This systematic review explores the role of microbiome dysbiosis in colorectal cancer (CRC) development and progression, with a focus on microbiome-based biomarkers for early detection. It evaluates laboratory-based research on how microbiome alterations contribute to CRC risk, highlights methodological approaches for microbiome analysis, and identifies strengths and limitations in current research. The findings suggest that microbiome-based biomarkers hold promise for early CRC diagnosis and treatment. Nevertheless, there is a need for future research to refine these biomarkers, integrate them into existing diagnostic methods, and better understand the mechanisms of microbiome-related CRC progression to enhance prevention, diagnosis, and management strategies.